1985
DOI: 10.1121/1.391993
|View full text |Cite
|
Sign up to set email alerts
|

Impact noise and the equal energy hypothesis

Abstract: The equal energy hypothesis (EEH) was evaluated over a limited range of conditions by exposing four groups of chinchillas to impact noise (200-ms B duration) presented at a fixed rate of four impacts per second. The intensity of the impacts (107-125 dB peak SPL) and the duration (120-1.87 h) of the four exposure conditions were counterbalanced so that the four groups received the same total energy. The traumatic power of the exposures was assessed by measuring the threshold shift of the auditory evoked respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Although the amount of hair cell damage varied somewhat across the five subjects exposed to the 80-dB SPL noise, the degree of variability was similar to that seen in other studies of acoustic trauma. 26 Fig 3, right, the IHCs and pillar cells are intact, although several pillar cell processes are again swollen. Missing OHCs have been replaced by pro¬ cesses of supporting cells, ie, OHC1 by outer pillar cells and OHC2 and OHC3 by Deiters' cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although the amount of hair cell damage varied somewhat across the five subjects exposed to the 80-dB SPL noise, the degree of variability was similar to that seen in other studies of acoustic trauma. 26 Fig 3, right, the IHCs and pillar cells are intact, although several pillar cell processes are again swollen. Missing OHCs have been replaced by pro¬ cesses of supporting cells, ie, OHC1 by outer pillar cells and OHC2 and OHC3 by Deiters' cells.…”
Section: Resultsmentioning
confidence: 99%
“…Industrial noise containing sudden sound pressure peak levels may, however, pose an increased risk for noise-induced permanent threshold shift that cannot be predicted from continuous noise with equal energy (8,9,28,35,50,51,53). This possibility has been illustrated in laboratory studies on animals (17,31,43), but also contradictory and nonconclusive reports have been presented (3,9,16,19). Moreover, it has been suggested that simultaneous exposure to hand-arm vibration may also aggravate noise-induced permanent threshold shift (20,30,33,41,42,52).…”
mentioning
confidence: 89%
“…Although the equal energy principle is ge nerally accepted as a basis for assess ing both sound pressure energ y and the risk of hearing loss in the case of steady noise (13,17), inconsistencies still exist in the application of the equal energy princi ple to impulse noise (3,10,13,15). Recent animal studies have given co ntrove rsia l res ults wit h regard to dama ge ca used to the inner ear by impulse noise, and in many studies find ings do not support the equal energy principle very strongly (9,10,15,27 ). It has been sugges ted that the hazard from low-frequ ency impulses is une xpectedl y low compared with the risk ass ociated with higher frequency impul ses (9,15).…”
Section: Effective Duration Of Exposure To Shooting Noisementioning
confidence: 99%
“…This adjusted average duration of exposure was 22.0 (SD 2.6, range 16.2-27.2) years for personally fired shots and 61.0 (SD 4.4, range 41.5-69.7) years for all of the shots fired and supervised by the officers. With all types of noise, the adverse effects on hear- the total energy of noise (27), and the equ al ene rgy principle has been proposed also for the risk assessment of weapon impulses (17). Damage risk cr iteria proposed for weapon impulses are based on the duration and numb er of impul se s ( 13,26) and also on the hear ing protection employe d (6,23) .…”
Section: Effective Duration Of Exposure To Shooting Noisementioning
confidence: 99%